Авторська ремарка як різновид паратексту в п’єсах «Орфей спускається у пекло» Теннессі Вільямса і «Сваха» Торнтона Вайлдера - Гнатко, Лідія Володимирівна; Hnatko, L. V. (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті досліджено авторську ремарку як різновид пара тексту в п’єсах «Орфей спускається у пекло» Теннессі Вільямса і «Сваха» Торнтона Вайлдера. Визначено різновиди ремарок у драматичних творах залежно від їхнього розташування і проведено аналіз щодо виявлення позамовних стилістичних засобів характеристики дійових осіб у середовищі їхнього спілкування. The article deals with the research of stage directions as a varietz of paratext in Tennessee William’s «Orpheus Descending» and Thornton Wilder’s «The Matchmaker». The Variety of stage directions in drama is defined in compliance with their location, such as: «the interior», «an introduction of the actor», «сharacters’ emotional state», «сharacters’ movement», «the musical accompaniment». Extralinguistic means of the personages’ characterization in the communicative aspect are noted, since stage directions play a significant role in the characterization of situations and personages’ emotionality. The linguostylistic and pragmatic features of stage directions are compared. Thus, among the dominant linguostylistic means used in stage directions we have traced: epithed, metaphor and simile. Stage directions are also discussed in the context of their volume and special stylistic shading, suggesting that they may be regarded as a kind of artistic prose text.
Stage Directions as a Variety of Paratext in Tennessee Williams’s “Orpheus Descending” and Thornton Wilder’s “The Matchmaker”
Keywords: ремарка; stage direction; паратекст; paratext; персонаж; character